2013
DOI: 10.1016/j.bbadis.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin supplementation is effective in improving mitochondrial dysfunctions induced by 3-nitropropionic acid: Implications in Huntington's disease

Abstract: The study was designed to investigate the beneficial effect of quercetin supplementation in 3-nitropropionic acid (3-NP) induced model of Huntington's disease (HD). HD was induced in rats by administering sub-chronic dose of 3-NP, intraperitoneally, twice daily for 17days. Quercetin was supplemented at a dose of 25mg/kg body weight by oral gavage for 21days. At the end of treatment, mitochondrial bioenergetics, mitochondrial swelling, oxidative stress, neurobehavioral deficits and histopathological changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 58 publications
4
62
0
Order By: Relevance
“…It is well known that, mitochondrial oxidative stress is recognized to play an important role in HD pathology [11]; therefore, supplementation with antioxidants that could attenuate mitochondrial oxidative stress may improve mitochondrial lipid composition. Several therapeutic approaches, which could interfere with mechanisms involved in HD progression, are currently being investigated [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that, mitochondrial oxidative stress is recognized to play an important role in HD pathology [11]; therefore, supplementation with antioxidants that could attenuate mitochondrial oxidative stress may improve mitochondrial lipid composition. Several therapeutic approaches, which could interfere with mechanisms involved in HD progression, are currently being investigated [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that quercetin possesses efficient antioxidant activity [21][24]. Animal experiments suggest that quercetin protected the brain, liver, and other tissues against oxidative stress induced by ischemia-reperfusion injury, toxic compounds and other factors [22][24].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the data are related to the potential of flavonoids to prevent cognitive deficits or rescue learning and memory impairments in pathological contexts, including animal models for Alzheimer’s (Gu et al, 2016), Parkinson’s (Antunes et al, 2014) and Huntington’s diseases (Sandhir and Mehrotra, 2013) and in Multiple Sclerosis (Makar et al, 2016). Nevertheless, it has been showed that these compounds may also improve the cognitive ability of healthy young and old animals (van Praag et al, 2007; Williams et al, 2008; Rendeiro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%